Highly Dispersed Re-Doped CoAl2O4 Nanopigments: Synthesis and Chromatic Properties. (16th March 2016) - Tong, Yuping; Zhang, Hailong; Wang, Shun; Chen, Zheng; Bian, Baixue
Abstract : Nanosized spinelC o A l 2 - x R e x O 4 complex oxides were prepared by self-propagation combustion method. The products have been characterized by XRD, SEM, and EDS. The results indicated that Al 3+ can be partly replaced by Re 3+ when the doped amount is less than 10%, which forms single solid solution. The NIR reflectance and chromatic properties of samples have also been investigated. The substitution of Re 3+ for Al 3+ in CoAl2 O4 can increase the blueness of pigments. SEM results revealed that the obtainedC o A l 2 - x R e x O 4 pigments consisted of highly dispersed spherical-like nanoparticles with uniform size distribution. EDS results indicated that the distribution of element was considerably uniform with no chemical segregation phenomenon.